2003
DOI: 10.1096/fj.02-1194com
|View full text |Cite
|
Sign up to set email alerts
|

Does metabolic radiolabeling stimulate the stress response? Gene expression profiling reveals differential cellular responses to internal beta vs. external gamma radiation

Abstract: DNA microarray analyses were used to investigate the effect of cell-incorporated 35S-methionine on human colorectal carcinoma cells. This beta-radiation-induced gene expression profile was compared with that induced by external gamma-radiation. The extent of DNA fragmentation was used as a biomarker to determine the external gamma dose that was bioequivalent to that received by cells incubated in medium containing 35S-methionine. Studies showed that 35S-methionine at 100 microCi/mL induced a much more robust t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…It was therefore somewhat surprising that only 0.5% of the total number of all known and predicted genes in the human genome were responsive to 125 I-IUdR-triggered damage, whereas the expression of about 5% of human genes was changed by γ-radiation exposure. In contrast, a previous study indicated that β-radiation-induced gene expression profile of cell-incorporated [ 35 S]methionine induced a much more robust transcriptional response than γ-radiation in human colorectal carcinoma cells (Marko et al, 2003). One of the key differences between 125 I-IUdR and [ 35 S]methionine irradiations is the intracellular distribution of these compounds; that is, 125 I-IUdR is incorporated into DNA whereas [ 35 S]methionine is deposited in both the cytoplasm and nucleoplasm.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It was therefore somewhat surprising that only 0.5% of the total number of all known and predicted genes in the human genome were responsive to 125 I-IUdR-triggered damage, whereas the expression of about 5% of human genes was changed by γ-radiation exposure. In contrast, a previous study indicated that β-radiation-induced gene expression profile of cell-incorporated [ 35 S]methionine induced a much more robust transcriptional response than γ-radiation in human colorectal carcinoma cells (Marko et al, 2003). One of the key differences between 125 I-IUdR and [ 35 S]methionine irradiations is the intracellular distribution of these compounds; that is, 125 I-IUdR is incorporated into DNA whereas [ 35 S]methionine is deposited in both the cytoplasm and nucleoplasm.…”
Section: Discussionmentioning
confidence: 63%
“…A wide variety of the genotoxic agents exists; among them ionizing radiation (IR) being one of the best studied. IR is shown to elicit various cellular responses resulting in increases of gene mutation rate, oncogenic transformation, cell death, changes in gene expression and other (Amundson et al, 1999;Marko et al, 2003;Amundson et al, 2004;Rieger and Chu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This rapid delivery of radiation bears little resemblance to the dose-rate when using targeted radionucleotides, whereby the tissue-absorbed dose of radiation is delivered mainly in the form of ␤-emissions, and the rate of deposition of radiation energy in the tissues is much slower than with external beam ␥-radiation. 30 Considering this extreme difference in radiation dose rate, as well as published studies showing that cells respond differently to ␤ versus ␥ radiation, it is significant that we have now demonstrated that PS-341 can also sensitize myeloma cells to the lethal effects of a ␤-emitting isotope.…”
Section: Discussionmentioning
confidence: 98%
“…γ-rays, β-particles, α-particles) influences the regulation of the PBRs. There is evidence to suggest that, at least in irradiated cells, radiation type can have a significant impact on cellular responses not only with respect to the number of genes induced, but also with respect to the level of gene induction [75]. Table 1).…”
Section: Co-culturementioning
confidence: 99%